Entrepreneurship and Marketing Training for Women MSME (Micro, Small and Medium Enterprises) Actors in Gampong Suak Bilie, Suka Makmue District, Nagan Raya Regency - Edi Wanda; Genius Umar; Rahmat Oriza; Firdaus (CV. Naskah Aceh, 2024)
Women Micro, Small and Medium Enterprises (MSMEs) play an important role in supporting the local economy, especially in rural areas such as Gampong Suak Bilie, Suka Makmue Sub-district, Nagan Raya District. However, challenges in business management, marketing strategies, and entrepreneurship development often become obstacles in optimizing their potential. This community service aims to provide effective entrepreneurship and marketing training to female MSME players in Gampong Suak Bilie. The training is designed to improve their skills in planning, managing, and marketing products more professionally, both online and offline. The training methods used include theory sessions, hands-on practice, and group discussions to encourage active participation. In addition, the training also provides assistance in implementing digital marketing strategies to expand market reach. It is expected that with this training, women MSME players will be able to increase the competitiveness of their businesses, develop a wider marketing network, and increase income in a sustainable manner. The results of this activity will be measured through increased understanding and entrepreneurial skills as well as increased product sales from the participants. Thus, this program is expected to make a real contribution to women's economic empowerment in Gampong Suak Bilie.